Game theory anticipating reactions for winning actions - Burkey, Mark L. (2013 digital library., 2013)
From its beginnings in the early 1900s, game theory has been a very mathematical, technical subject. However, it also provides valuable, everyday lessons that are important for managers and executives to understand. Current books and textbooks are mostly highly mathematical, and almost all are very long. This primer will deliver a focused and precise, largely nonmathematical overview of topics in game theory that are directly relevant managers and professionals in many fields.